ANALYSIS OF HEALTH SERVICE QUALITY BASED ON SERVQUAL DIMENSIONS AT UPTD HEALTH CENTER TEGALBULEUD SUKABUMI REGENCY - Riki Windiansah; Tuah Nur; Yana Fajar FY Basori (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Healthcare service quality is a key indicator for evaluating the effectiveness of public service delivery in the health sector. As a primary healthcare facility, the Community Health Center (Health Center) is expected to provide high-quality, professional, and patient-oriented services to meet community needs. This study aims to analyze the quality of healthcare services at the UPTD Tegalbuleud Community Health Center, Sukabumi Regency, based on the five SERVQUAL dimensions, namely Tangibles, Reliability, Responsiveness, Assurance, and Empathy, and to identify the supporting and inhibiting factors affecting service quality. This study employed a descriptive qualitative approach. Data were collected through observations, in-depth interviews, and documentation involving the head of the community health center, healthcare professionals, administrative staff, and patients selected using purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data collection, data condensation, data display, and conclusion drawing and verification. Data credibility was ensured through source triangulation, technique triangulation, and member checking. The findings indicate that the overall quality of healthcare services at the UPTD Tegalbuleud Community Health Center has been implemented effectively across all SERVQUAL dimensions. However, several challenges remain, including inadequate waiting room facilities, limited healthcare personnel, and high patient volumes that affect service responsiveness. Supporting factors include healthcare personnel competency, the implementation of standard operating procedures, and organizational commitment to continuous service quality improvement. The findings provide practical implications for healthcare managers and local governments in developing strategies to enhance patient-centered healthcare service quality.